Business Income Analysis of Kelompok Tani Hutan (KTH) Majojo Tuguwaji Village, Tidore Islands City - Hakim, Jadia; Azizah HS, Nur; Putri , Wiwin Failysa (Agrikan Jurnal Agribisnis Perikanan, 2025)
Non-Timber Forest Products (NTFPs) are types of plants that grow both inside and outside forest areas. NFPs or Non-Tinber Forest Products have a very strategic value. NFPs are a group of farmers or individuals who group themselves and manage forestry businesses both inside and outside forest areas which include timber forest product businesses, non-timber forest products, and environmental services to improve welfare based on the principles of family, welfare, equality, participation and self-reliance. KTH Majojo is located in Tuguwaji Village, Tidore District, Tidore Islands City. The products produced by KTH Majojo are non-timber forest products. This research was conducted from July to August 2024. Research Location At KTH Majojo, Tuguwaji Village, Tidore Islands City. This location was chosen as the research location because it was to see the income of the products produced by KTH Majojo. The results of this study indicate that the products produced by KTH Majojo are: Guraka Water, Sarabati, Gura Coffee and Kua Rujak from several products produced by KTH Majojo, which had an income in 2023 of IDR 7,325,000, which was obtained from the total income (TR) of IDR 18,000,000 minus the total cost (TC) of IDR. 10. 675,000 thus the income obtained during the implementation of production activities for 3 times in 2023, namely in February, June and September is Rp. 2,441,666, while the average monthly income is Rp. 610,000